Inclusive Governance in Institutional Management of the Water Sector in North Macedonia - Panov Angelcho; Rustemi Agron (SEEU Review)
This paper examines the legislative and institutional framework for water management in North Macedonia, emphasizing gender and social inclusion. The Law on Waters establishes the legislative basis, with the Government defining river basin districts and adopting the National Strategy and Water Master Plan. The Ministry of Environment and Physical Planning (MoEPP) oversees water management activities, including granting concessions, adopting river basin management plans, and setting water quality standards. However, the MoEPP’s capacity is insufficient to meet all obligations in line with the principles of Leave No One Behind (LNOB) and Gender Equality (GE).